Visual basic - Monterrubio, Andrés (My University, 1994)
Starting visual basic: when you run the visual basic setup program. Setup automatically creates a new program group and new programs items for visual basic in windows. You are then ready to start visual basic from windows. To start visual baisc from windows: double click the visual basic icon. You can also star visual basic from either the file manager or the ms-dos prompt.
Keywords: toolbox; properties window; custom controls; position and size coordinates; building a simple visual basic application; event- driven; procedural applications